Trust in Conventional Healthcare and Utilization of Complementary and Alternative Medicine in South Tyrol, Italy: A Population-Based Cross-Sectional Survey - Barbieri, Verena; Lombardo, Stefano; Gärtner, Timon; Piccoliori, Giuliano; Engl, Adolf; Wiedermann, Christian J. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. This study explored the link between trust in conventional healthcare and consultations with complementary and alternative medicine (CAM) providers in South Tyrol, Italy’s linguistically diverse region.Methods. A representative cross-sectional survey of 1,388 South Tyrolean adults assessed trust in conventional healthcare, general practitioners, and complementary and alternative medicine consultation frequencies and their determinants using chi-square tests and Kendall-Tau-b correlations.Results. Seventy percent trusted the traditional healthcare system, with general practitioners as the primary trusted professionals. Trust is correlated with higher education and linguistic compatibility. A 5% subgroup, mostly women and multilinguals with lower education levels, showed uncertain trust. Over 80% had seen a general practitioner in the last year, while distrust was correlated with complementary and alternative medicine consultations. German and Ladin speakers, with higher education levels, were notably inclined towards complementary and alternative medicine consultations.Conclusions. Trust in South Tyrolean healthcare varied according to education level and language. While general practitioners remain central, there is a marked shift towards complementary and alternative medicine among specific groups.